Temporality and Self-Affirmation: A Kierkegaardian Critique of Nietzsche's Doctrine of the Eternal Recurrence of the Same - Hinman, Lawrence M. (KIERKEGAARDIANA, 1980)
Temporality and Self-Affirmation: A Kierkegaardian Critique of Nietzsche's Doctrine of the Eternal Recurrence of the Same